Adolescent male hazardous drinking and participation in organised activities: Involvement in team sports is associated with less hazardous drinking in young offenders. (16th May 2014) - Hallingberg, Britt; Moore, Simon; Morgan, Joanne; Bowen, Katharine; van Goozen, Stephanie H. M.
Abstract Background There is a lack of research investigating organised activity participation and associated alcohol use in vulnerable groups. Aims The purpose of this research was to test and compare associations between participation in organised activities and indicators of hazardous drinking between young offenders and young non‐offenders. Methods Two groups of 13–18 year‐old males were recruited in Cardiff, UK: 93 young offenders and 53 non‐offenders from secondary schools matched on estimated IQ, sex and socioeconomic status. Indicators of hazardous drinking were measured using the Fast Alcohol Screening Test (FAST). Organised activity participation and externalising behaviour was measured by the Youth Self Report. The Wechsler Abbreviated Scale of Intelligence was also administered. Results Young offenders participated in fewer organised activities and had higher FAST scores than non‐offenders. Young offenders and non‐offenders significantly differed on mean FAST scores if they participated in no organised activities but not if they participated in at least one team sport. Externalising behaviour problems were unrelated to participation in organised activities. Conclusions Although young offenders were less likely to have participated in organised activities, for them, participation in a team sport was associated with less hazardous drinking. Vulnerable youths who might benefit most from sporting activities actually access them the least. Future research should identify the different barriers to participation that they face. © 2014 The Authors. Criminal Behaviour and Mental Health published by John Wiley & Sons Ltd.